2019
DOI: 10.1002/hbm.24609
|View full text |Cite
|
Sign up to set email alerts
|

Precentral degeneration and cerebellar compensation in amyotrophic lateral sclerosis: A multimodal MRI analysis

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive and intractable neurodegenerative disease of human motor system characterized by progressive muscular weakness and atrophy. A considerable body of research has demonstrated significant structural and functional abnormalities of the primary motor cortex in patients with ALS. In contrast, much less attention has been paid to the abnormalities of cerebellum in this disease. Using multimodal magnetic resonance imagining data of 60 patients with ALS and 60 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 74 publications
4
39
0
Order By: Relevance
“…Our findings of significant microstructural abnormalities in the bilateral CST and the middle posterior body of the CC in ALS revealed by decreased FD are consistent with previous reports using DTI and high-angular resolution diffusion imaging (HARDI) ( Kalra et al, 2020 , Kassubek et al, 2018 , Müller et al, 2020 , Müller et al, 2016 , Qiu et al, 2019 , Trojsi et al, 2017 , Trojsi et al, 2013 ). Specifically, some HARDI studies showed a highly significant decrease of generalized FA and fiber length and density in the CST and CC ( Trojsi et al, 2017 , Trojsi et al, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings of significant microstructural abnormalities in the bilateral CST and the middle posterior body of the CC in ALS revealed by decreased FD are consistent with previous reports using DTI and high-angular resolution diffusion imaging (HARDI) ( Kalra et al, 2020 , Kassubek et al, 2018 , Müller et al, 2020 , Müller et al, 2016 , Qiu et al, 2019 , Trojsi et al, 2017 , Trojsi et al, 2013 ). Specifically, some HARDI studies showed a highly significant decrease of generalized FA and fiber length and density in the CST and CC ( Trojsi et al, 2017 , Trojsi et al, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…A total of 120 right-handed subjects, including 60 patients with ALS (39 males, mean age 48.77 years old, range 26–69) and 60 healthy controls (39 males, mean age 48.15 years old, range 24–70), were included in this study. These subjects had also participated in our previous neuroimaging study ( Qiu et al, 2019 ). Briefly, all patients with ALS met the El Escorial criteria for probable or definite ALS ( Brooks et al, 2000 ) and were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…Previous rs-fMRI studies in ALS have primarily reported the involvement of both motor and extra-motor brain regions i.e. the precentral gyrus, supplementary motor area, frontal, temporal, parieto-occipital areas and the cerebellum ( Mohammadi et al, 2009 , Jelsone-Swain et al, 2010 , Verstraete et al, 2010 , Agosta et al, 2011 , Agosta et al, 2013 , Douaud et al, 2011 , Luo et al, 2012 , Tedeschi et al, 2012 , Zhou et al, 2013 , Zhou et al, 2016 , Heimrath et al, 2014 , Chenji et al, 2016 , Menke et al, 2016 , Qiu et al, 2019 ). Additionally, structural MRI studies have reported grey matter (GM) alterations in cortical brain areas i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The cerebellum is considered a crucial subcortical brain structure responsible for not only controlling movement, but also for maintaining higher-level cognitive functions ( Schmahmann and Sherman, 1998 , Middleton and Strick, 2000 , Strick et al, 2009 , Buckner, 2013 , Koziol et al, 2014 , Moberget and Ivry, 2019 ). The involvement of the cerebellum has been frequently studied in other neurodegenerative disorders ( Fasano et al, 2017 , Mormina et al, 2017 , Tona et al, 2017 , Bharti et al, 2019 , Qiu et al, 2019 ); however, no neuroimaging study in ALS has so far investigated, as its primary focus, the cerebellum and its connection with the rest of the brain. Thus, to address this gap in knowledge, we specifically targeted the deep brain cerebellar nuclei and in particular the dentate nucleus (DN) to investigate the structural and functional MRI alterations in the cortical and subcortical brain structures of the cerebral cortex.…”
Section: Introductionmentioning
confidence: 99%
“…It is speculated that these changes may be related to the functional compensation or the reorganization of the cerebral structure in ALS (60,61). In agreement with this speculation, several compensatory phenomena, as reflected by the increased gray matter volume or the overactivation of specific brain regions (62,63), have been demonstrated in ALS.…”
Section: Discussionmentioning
confidence: 71%